2010
DOI: 10.1177/1368430210371639
|View full text |Cite
|
Sign up to set email alerts
|

Relative deprivation and intergroup competition

Abstract: Two experiments utilized a new experimental paradigm -the IPD-MD game -to study how relative deprivation at the group level affects intergroup competition. The IPD-MD game enables group members to make a costly contribution to either a within-group pool that benefits fellow in-group members, or a between-group pool, which, in addition harms out-group members. We found that when group members were put in a disadvantaged position, either by previous actions of the out-group (Experiment 1) or by random misfortune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 64 publications
6
72
0
1
Order By: Relevance
“…By using systematic variations of the intergroup context in which the social dilemma was embedded, this research provided insight into how contributions to public goods, which influence both in-group and out-group members, shape social perceptions. Second, we extend recent research on social motives in intergroup conflict (De Dreu, 2010;De Dreu et al, 2010;Halevy et al, 2008Halevy et al, , 2010Halevy, Weisel, & Bomstein, 2011) by showing that the structure of an intergroup conflict (e.g., IPD vs. IPD-MD vs. nested social dilemma) has important consequences not only on intergroup behavior and the conflict's outcomes but also on social perceptions, attributions, and actions, and through them, on intragroup processes such as the emergence of social hierarchy. Finally, we contribute to the literature on social hierarchy by illustrating the usefulness and importance of decomposing status into prestige and dominance (Cheng et al, 2010;Henrich & Gil-White, 2001).…”
Section: Theoretical Implicationssupporting
confidence: 75%
See 1 more Smart Citation
“…By using systematic variations of the intergroup context in which the social dilemma was embedded, this research provided insight into how contributions to public goods, which influence both in-group and out-group members, shape social perceptions. Second, we extend recent research on social motives in intergroup conflict (De Dreu, 2010;De Dreu et al, 2010;Halevy et al, 2008Halevy et al, , 2010Halevy, Weisel, & Bomstein, 2011) by showing that the structure of an intergroup conflict (e.g., IPD vs. IPD-MD vs. nested social dilemma) has important consequences not only on intergroup behavior and the conflict's outcomes but also on social perceptions, attributions, and actions, and through them, on intragroup processes such as the emergence of social hierarchy. Finally, we contribute to the literature on social hierarchy by illustrating the usefulness and importance of decomposing status into prestige and dominance (Cheng et al, 2010;Henrich & Gil-White, 2001).…”
Section: Theoretical Implicationssupporting
confidence: 75%
“…Contributions to the within-group pool in this game are considered manifestations of "in-group love," whereas contributions to the between-group pool are considered manifestations of "outgroup hate" (De Dreu, 2010;De Dreu et al, 2010;Halevy et al, 2010). Thus, by using the IPD-MD game.…”
Section: Study 2: Status Conferral As a Function Of In-groupmentioning
confidence: 99%
“…And Smith and colleagues (1994) presented group members with distributions of participant payments that paid many more outgroup members in comparison to ingroup members as a manipulation of GRD. Experimental manipulations like these could enable researchers to test many of the basic casual relationships presumed by RD models (also see Folger, 1987;Grant & Brown, 1995;Guimond & Dambrun, 2002;Halevy et al, 2010;Martin, 1986aMartin, , 1986b.…”
Section: Limitationsmentioning
confidence: 99%
“…A large corpus of research, mostly of a corre lational nature, has demonstrated that the more individuals feel collectively deprived, the more they show prejudice against minority or stigmatized outgroups (Dambrun, Taylor, et al, 2006;Vanneman & Pettrigrew, 1972). Moreover, relative de privation leads members to engage in intergroup competition to a considerable extent (Halevy, Chou, Cohen, & Bornstein, 2010). Nevertheless, the few studies including relative gratifi cation and relative deprivation in the same design have revealed that the relationship between deprivation/gratification and in tergroup attitudes is not linear (a phenomenon named the "Vcurve" effect; Dambrun & Taylor, 2013;Dambrun, Taylor, et al, 2006;Grofman & Muller, 1973).…”
Section: Relative Deprivation and Relative Gratificationmentioning
confidence: 99%